Towards developing a 21st century curriculum through the perspective of the community of inquiry (CoI) framework - Mumuni Baba Yidana; Gabriel Kwasi Aboagye (Cogent Social Sciences, 2024)
Even though previous literature points to the significance of establishing the cognitive, social and teaching presences of students, there is still scanty research in relation to how the higher education curriculum could assist the 21st century student develop 21st century skills through the establishment of the cognitive, social and teaching presences through the perspective of the Community of Inquiry Framework. Also, such research is complex, limited and highly contested within the higher education landscape in the sense that there are dissenting views about establishing these presences. In order to address this literature gap, the partial least squares structural equation modelling (PLS-SEM) was used to unveil how the cognitive presence, social presence and teaching presence inform the development of a holistic curriculum in the 21st century. The instrument used as the research tool was adapted from the original CoI framework survey. Using the descriptive correlational research design, survey data was elicited from 807 students who were proportionately stratified into male and female. It emanated from the study that there is a statistically significant relationship between the cognitive, social and teaching presences of students and the development of 21st century skills in the higher education curriculum. It is therefore recommended that curriculum developers should ensure a holistic development of the higher education curriculum by ensuring that all the presences are duly established. Lecturers should also endeavor to ensure that each of these presences is established in their lessons to promote lifelong learning by way of enhancing the 21st century curriculum.